Essentialization of Social Categories Across Development in Two Cultures. Issue 1 (15th January 2019) - Davoodi, Telli; Soley, Gaye; Harris, Paul L.; Blake, Peter R.
Abstract : Children display an "essentialist" bias in their everyday thinking about social categories. However, the degree and form of this bias varies with age and with the nature of the categories, as well as across cultures. This project investigated the development of the essentialist bias across five social categories (i.e., gender, nationality, religious affiliation, socioeconomic status (rich/poor), and sports‐team supporter) in two countries. Children between 5 and 10 years of age in Turkey (Study 1, N  = 74) and the United States (Study 2, N  = 73), as well as adults in both countries (Study 3, N  = 223), participated. Results indicate surprising cross‐cultural parallels with respect to both the rank ordering of essentialist thinking across these five categories and increasing differentiation among them over development.